The Voice of Travelers : Leveraging User-Generated Content for Tourism Development 2018 - Salem, Talia; Twining-Ward, Louise (World Bank, Washington, DC, 2018)
Tourism is growing faster than ever before in emerging and developing economies. In just 10 years, the tourism landscape has changed completely. Digital platforms are changing the way travel is traditionally researched, bought, sold, experienced and shared. Facilitated by digital platforms, user-Generated Content (UGC) is fast becoming the most important and widely used source of travel information. This impacts the traveler's path to purchase and disrupts established travel agencies, guidebooks, conventional marketing approaches and star rating systems. It also presents new opportunities for developing destinations to leverage these platforms for big data and cost-effective performance improvements. The World Bank Group and TripAdvisor collaborated on this report to support destination management organizations and local suppliers to extract the most value from UGC, while avoiding its pitfalls. This body of work aims to highlight good practices and suggest tools to consider when building plans for managing online reputation. It also provides case studies that illuminate effective campaigns and investment. The report is intended for use by those involved in or responsible for the management and/or marketing of a destination or a tourism business, with a focus on the leisure-travel market.